Public perceptions of challenges facing inclusive governance of hot spring landscapes in China - Li, Yue; Yuan, Yue; Abu Bakar, Nor Azlina; Mundher, Riyadh; Yue, Guo (Frontiers in Environmental Science, 2025)
Recognizing the ecological and cultural significance of hot springs, the Chinese government has adopted protective legislation. However, these measures are being undermined by local governments’ failure to adopt Inclusive Landscape Governance (ILG). Therefore, this research aims to provide an understanding of public views on the challenges facing the implementation of inclusive governance for the protection and management of hot spring landscapes in Linyi City, China. Inclusive governance requires the participation of multiple public stakeholders—including residents, local business owners, and tourists—in decision-making processes. This qualitative study employed semi-structured interviews to gather insights from public stakeholders in Linyi City, China. A coding process was used to analyze the interviews, and the data were examined to identify challenges to inclusive governance. The analysis revealed eight challenges: lack of shared responsibility, ineffective planning and management, complex relationships and trust, knowledge variability and limited awareness, differing levels of interest and need, policy deficiencies, development concerns, and limited public participation. By identifying these challenges, this research contributes to the development of more effective strategies for inclusive governance, ultimately promoting the sustainable management of hot springs.